Modelagem da dispersão de poluentes em meios porosos: caso do aterro de resíduos solidos urbanos de Jacarezinho (PR) - Fandino, Jonathan Steven Murcia (2020)
Municipal solid waste (MSW) disposal systems are still a sanitary and environmental problem. The high concentration of recalcitrant and toxic substances present in liquids arising from the decomposition of waste, mixed or not with rainwater, presents a risk to human health and the environment. Waterproofing systems are not always available or working properly so that leachate can seep into the ground and reach groundwater, contaminating it. It is necessary to establish mechanisms to predict leachate dispersion in order to determine possible scenarios and control systems. The present work aimed to model the dispersion of leachate from urban solid waste through saturated soil in a case study. The research method included the definition of conceptual and numerical models, numerical simulation and validation. As a case study, we used the municipal landfill of Jacarezinho in southern Brazil. The conceptual model was based on existing data from geology, hydrology, hydrogeology and leachate characterization. Two sources of pollution were considered: waste disposal area and wastewater treatment area. The codes MODFLOW and MT3DMS were used and the dispersion of pollutants Cr, Pb, Cu, and Zn was simulated. Pollutant mass concentration fields were calculated at different times: 1, 5, 10, 25 and 50 years. The results indicated that the pollutants can reach the nearest water body of the landfill, the Ouro Grande river, in a period of 5 years, and a respective tributary in a period of 1 year of the initial generation of leachate. The pollutants in the Ouro Grande River (P2) reached 0.006% of the initial value of the source concentration and dispersed in higher concentrations in the second theoretical soil layer that comprised 2 to 10 meters deep. The mass flow of Zn was calculated seven times higher than the other pollutants. For the final period of the simulation, the tributary of the Ouro Grande River received Cu and Pb concentrations that exceeded the maximum values allowed in Brazilian legislation to meet the watercourse quality standard. Regarding the potability standard, Pb was the only pollutant analyzed that exceeded the reference values. The calculated pollutant concentrations did not exceed the limits of the liquid effluent release standard established by Brazilian legislation. From the simulation performed, it was concluded that the Jacarezinho landfill has the potential for pollution of the surrounding soil and groundwater.